Soil organic carbon in drylands: shrub encroachment and vegetation management effects dwarf those of livestock grazing. Issue 7 (26th May 2020) - Throop, Heather L.; Archer, Steven R.; McClaran, Mitchel P.
Abstract: Dryland ecosystems occur worldwide and play a prominent, but potentially shifting, role in global biogeochemical cycling. Widespread woody plant proliferation, often associated with declines in palatable grasses, has jeopardized livestock production in drylands and prompted attempts to reduce woody cover by chemical or mechanical means. Woody encroachment also has the potential to significantly alter terrestrial carbon storage. However, little is known of the long‐term biogeochemical consequences of woody encroachment in the broader context of its interaction with common dryland land uses, including "brush management" (woody plant clearing) and livestock grazing. Present assessments exhibit considerable variation in the consequences of these land use/land cover changes, with evidence that brush management may counteract sizeable impacts of shrub encroachment on soil biogeochemical pools. A challenge to assessing the net effects of brush management in shrub‐encroached grasslands on soil organic carbon (SOC) and total nitrogen (N) pools is that land management practices are typically considered in isolation, when they are co‐occurring phenomena. Furthermore, few studies have assessed spatial patterns in brush management and how these are affected in decades following treatment on sites with contrasting grazing histories. To address these uncertainties and interactions, we quantified the impacts of shrub encroachment and their subsequent mortality resulting from brush management (herbicide application) on SOC and N pools in a Sonoran Desert grassland where long‐term grazing manipulations (>100 yr) co‐occur with shrub encroachment and brush management. Pools of SOC and N associated with herbicided shrubs declined markedly over ~40 yr, offsetting 66% of the increases from shrub encroachment. However, spatial patterns in SOC induced by shrubs persisted over the decades following brush management. Century‐long protection from grazing did little to change SOC and N pools. Accordingly, shrub encroachment and shrub mortality from brush management each far outweighed livestock grazing impacts. Consideration of the patterns of SOC and N through space (e.g., bole‐to‐dripline gradients), time (e.g., shrub age/size), land use (e.g., livestock grazing and brush management), and their interactions will position us to improve predictions of SOC and N responses to land use/land cover change, inform C‐based management decisions, and objectively evaluate trade‐offs with other ecosystem services.